Post Partum Care Practices among Postnatal Mothers in Tharu Community, Kailali District, Nepal - Gana, G (Journal of Chitwan Medical College, 2013)
Postnatal mothers are in high risk because most of the deaths occur in this period as compared to pregnancy and childbirth. The objectives of the research was to assess & find out the factors associated with post partum care practices among postnatal mothers and to suggest the measures for the utilization of post partum care services. A total of 175 respondents (all mothers having children below one year) were selected by using multi stage sampling technique from different wards of Dhangadi municipality, and Beladevipur, Geta, Phulbari, & Sripur VDCs of Kailali district from January to June, 2009. The data were statistically analyzed by using chi square test & Pearsons’ correlation test. Family income plays a significant role in Nutritious diet within 24 hours. Occupation had no effect on the frequency of postnatal visits. Education plays a significant role in changing perineal pad. Only 49.7% of respondents had done postnatal visit. Education plays significant role on colostrum feeding practices. Odds ratio = 4.09 (CI=32.06-55.34) at 95% confidence limit. Literate respondents have 4 times more practice of colostrum feeding as compared to illiterate. Distance plays a significant role in health facilities. Education of mothers play major role in postpartum care practices. DOI: http://dx.doi.org/10.3126/jcmc.v3i2.8438 Journal of Chitwan Medical College Vol.3(2) 2013 24-26